Relevansi Fraud Hexagon Theory terhadap Kecurangan Laporan Keuangan Pada Sektor Perbankan di Indonesia Tahun 2017-2021 - M Bagus Barezki; Luk Luk Fuadah; Anna Yulianita (Jurnal Informatika Ekonomi Bisnis, 2023)
This research aims to analyze the relevance of Fraud Hexagon Theory to financial statement fraud in the banking sector in Indonesia in 2017-2021. Agency theory explains that management has the ability to gain a lot of benefits for itself, so that management no longer acts in the interests of the principal, one way is through collusion. This research shows that financial target, external pressure, financial stability, director change, CEO photo change, and e-procement have a positive and significant effect on financial report fraud, while change in auditor and ineffective monitoring have a negative and insignificant effect on financial report fraud.